2015
DOI: 10.1111/jre.12285
|View full text |Cite
|
Sign up to set email alerts
|

Ridge augmentation using recombinant human fibroblast growth factor‐2 with biodegradable gelatin sponges incorporating β‐tricalcium phosphate: a preclinical study in dogs

Abstract: The combined use of rhFGF-2 and gelatin/β-TCP sponge promotes ridge augmentation in canine saddle-type bone defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 39 publications
2
26
1
Order By: Relevance
“…Compared to our previous study conducted under similar conditions, the amount of bone augmentation in the acidic group in the present study (total tissue height: 7.11 ± 0.69 mm; new bone height: 3.72 ± 0.58 mm) twelve weeks after operation was similar to the amount observed eight weeks after operation (total tissue height: 6.62 ± 0.66 mm; new bone height: 2.98 ± 0.65 mm). In the present study, bone height in the basic group (total tissue height: 6.63 ± 0.87 mm; new bone height: 2.88 ± 0.71 mm) was slightly higher than that in our previous study using acidic gelatin/β‐TCP sponges (IEP 5.0) with normal saline (total tissue height: 5.95 ± 0.74 mm; new bone height: 1.56 ± 0.66 mm) . These results indicate that the effectiveness of rhFGF‐2 release from basic gelatin/β‐TCP sponges (IEP 9.0) is detectable, albeit small.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…Compared to our previous study conducted under similar conditions, the amount of bone augmentation in the acidic group in the present study (total tissue height: 7.11 ± 0.69 mm; new bone height: 3.72 ± 0.58 mm) twelve weeks after operation was similar to the amount observed eight weeks after operation (total tissue height: 6.62 ± 0.66 mm; new bone height: 2.98 ± 0.65 mm). In the present study, bone height in the basic group (total tissue height: 6.63 ± 0.87 mm; new bone height: 2.88 ± 0.71 mm) was slightly higher than that in our previous study using acidic gelatin/β‐TCP sponges (IEP 5.0) with normal saline (total tissue height: 5.95 ± 0.74 mm; new bone height: 1.56 ± 0.66 mm) . These results indicate that the effectiveness of rhFGF‐2 release from basic gelatin/β‐TCP sponges (IEP 9.0) is detectable, albeit small.…”
Section: Discussioncontrasting
confidence: 70%
“…In vitro studies showed that acidic gelatin sponge (IEP 5.0) had a high affinity to rhFGF‐2, which is basic in vivo, and formed gelatin complexes ionically . The effect of controlled rhFGF‐2 release can be achieved by gelatin decomposition to enhance hard and soft tissue regeneration in in vivo studies . On the contrary, in vitro studies have reported that basic gelatin sponges (IEP 9.0) rarely have an affinity to rhFGF‐2 and do not exhibit polyion complexation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations